Masa Orientasi Siswa/Mahasiswa Sebagai Media Orientasi Pendidikan Tanpa Kekerasan - Hujair A.H. Sanaky (EL-TARBAWI, 2011)
Any kind of violence is not acceptable in any sort of values and rights, moreover if it occured in education circumstances. It is indeed against universal values and norms. Education is a medium and tool to internalize norms, good attitude and positive values into students personality. But it sometimes becomes dilematics when teachers find difficulties in doing the job, or when they deal with difficult students, should they use hard lead-to-violence way or soft way? This article found that no reason to use hard-violence way to deal with such problem. Teachers should use soft way to teach students to be pro-social with the spirit of nonviolence education. Doing so, education institutions (schools or higher educations) must provide standard operational procedure for teachers and provide a tools by which teachers can use to control any students activities that potentially leads to violence, verbally or phisically. In this way, law enforcement also takes an important part.